The effect of obesity on intrahepatic cytokine and chemokine expression in chronic hepatitis C infection. Issue 3 (15th March 2009) - Palmer, Clovis; Corpuz, Theresa; Guirguis, Marianne; O'Toole, Sandra; Yan, Kenneth; Bu, Yagmin; Jorgenson, John; Talbot, Michael; Loi, Kenneth; Lloyd, Andrew; Zekry, Amany
Abstract : Background: Obese subjects with chronic hepatitis C virus (HCV) infection have more rapidly progressive liver disease. Objective: In this study, we aimed to compare the hepatic cytokine and chemokine profiles in obese and lean subjects with chronic HCV infection using qRT-PCR and immunohistochemistry. Methods: Liver biopsies from 55 subjects were studied, including 20 with chronic hepatitis C, 25 with non-alcoholic fatty liver disease and 10 subjects with non-diseased liver. Results: Compared to the control groups, the liver injury in chronic hepatitis C was characterised by increased expression of several T-helper-1 cytokines including interferon-γ and tumour necrosis factor-α, and chemokines such as RANTES, IP-10 and MCP-1. In particular, in comparison with lean (BMI ≤25 kg/m 2 ) HCV infected subjects, obese (BMI≥30 kg/m 2 ) HCV infected subjects had increased hepatic expression of interferon-γ (p=0.004) and tumour necrosis factor-α (p<0.001), as well as increased expression of IP-10 (p=0.009) and MCP-1 (p<0.001). Localisation of these inflammatory chemokines revealed that in comparison to lean-HCV subjects, HCV infected liver from obese subjects exhibited significantly increased expression of IP-10 (p<0.001) and MCP-1 (p=0.02) in the inflammatory infiltrate of the portal tracts. In parallel, there was increased CD3 infiltration in the liver of obese-HCV subjects. Conclusions: The data provide important mechanistic information on the cause of hepatic injury in obese-HCV subjects including: (1) enhanced T helper-1 cytokine response patterns—to promote hepatocellular injury; (2) increased expression of the chemokines IP-10 and MCP-1 at both the mRNA and protein levels—to enhance inflammatory cell recruitment; (3) differing localisation of these chemokines within the liver of obese-HCV versus lean-HCV subjects—implying different inducing stimuli and; (4) increased CD3 expression in the liver of obese-HCV subjects—concordant with the increased expression of T cell chemoattractants.